Demethylation treatment restores erectile function in a rat model of hyperhomocysteinemia - Zhang, Zheng (Asian J Androl, 2016)
Methylation modification is an important cellular mechanism of gene expression regulation. Dimethylarginine dimethylaminohydrolase-2 (DDAH-2) protein is a pivotal molecular for endothelium function. To explore the effects of 5-aza-deoxycytidine (5-aza), a demethylation agent, in hyperhomocysteinemia (hhcy)-related erectile dysfunction (ED) rats, 5-aza (1 mg kg(−1)) was administrated to Sprague-Dawley hhcy-rats induced by supplemented methionine chow diet. Erectile function, nitric oxide-cyclic guanosine monophosphate (NO-cGMP) levels, expression of DDAH-2 protein and promoter methylation status of DDAH-2 were studied in the corpora cavernosa. We found that supplemented methionine diet induced a high homocysteine level after 6 weeks of treatment. DDAH-2 protein was down-regulated in the corpora cavernosa while the administration of 5-aza up-regulated DDAH-2 expression and restored erectile function. The methionine-fed rats showed high methylation levels of DDAH-2 promoter region while the group treated with 5-aza demonstrated lower-methylation levels when compared to the methionine-fed group. Besides, the administration of 5-aza improved NO and cGMP levels in methionine-fed rats. Therefore, the methylation mechanism involves in ED pathogenesis, and demethylation offers a potential new strategy for ED treatment.